The Feasibility of Guided Inquiry Based Powtoon Video Media Submatter Pressure Organism - Inggriani Inggriani; Kurnia Ningsih; Andi Besse Tenriawaru (Universitas Wiralodra, 2021)
This research aims to determine the feasibility of a video powtoon learning media application based on guided inquiry submater application of the concept of substance pressure in organism as a learning media for students and to find responses by students to the powtoon video media. This research is Research and Development (R&D) research with the Borg and Gall development model which consists of ten stages, this research has only reached the seventh stage which includes potentials and problems, data collection, product design, product validation, design revisions, product trials, and product revisions. The instruments used were the media validation sheet and the student response questionnaire validation sheet which was validated by 5 validators and the student response questionnaire. The subjects were students of class XI SMP Negeri 3 Pontianak. The validation results obtained CVR and CVI values, namely 1 which has met the minimum limit of 0.99 so that it is declared valid. The product trial obtained an overall average score for aspects (cognition, affection, conation) which was 83,57% so it is categorized as very strong. It can be concluded that the powtoon video media based on guided inquiry sub material is suitable for use as a learning medium.